Synthesis of Cr(III)-Morin Complex: Characterization and Antioxidant Study - Qadeer K. Panhwar; Shahabuddin Memon (The Scientific World Journal)
The complex formation between Cr(III) and morin was carried out in methanol and confirmed by analytical characterization using UV-Vis, IR, 1H NMR, and TG-DTA. UV-Vis shows significant bathochromic shift in benzoyl upon coordination as well as IR well illustrates the peak shift of C=O group and formation of a O–Cr(III) bond. Likewise, 1H NMR studies clarify that Cr(III) metal ion replaces the 5OH proton hence; 5-hydroxy-4-keto site is employed by morin in chelation to form six-membered stable ring system out of three available chelating sites. In addition, TG-DTA denotes the presence of coordinated and crystalline water molecules. The melting point of the complex was found to be 389°C by DSC. In addition, Cr(III)-morin complex was found to be a more potent antioxidant than morin as evaluated by DPPH• and FRAP methods.